Pharmacy calculations - Ballington, Don A.; McKennon, Skye A.; Ballington, Don A. (St. Paul, MN : Paradigm Education Solutions, 2017)
With Pharmacy Calculations for Technicians, students learn the essential mathematics concepts and skills pharmacy technicians use on the job. Clear, complete examples and practice problems guide students in learning the skills required for calculating and preparing drug doses in both community and institutional pharmacy settings. Students are guided step-by-step through calculation methods, including ratio and proportion, dimensional analysis, and alligation. -
Previous ed. published with title: Pharmacy math for technicians.
Includes index.
Keywords: Pharmaceutical arithmetic; Pharmaceutical arithmetic